2018
DOI: 10.1108/jpbm-01-2017-1388
|View full text |Cite
|
Sign up to set email alerts
|

Corporate brand transgression and punishing the transgressor: moderation of religious orientation

Abstract: Purpose With the aim of developing a better understanding of why some consumers still excuse corporate brands that engage in transgressions, this study tests whether extrinsically religious people tolerate corporate brands more than intrinsically religious individuals at different transgression levels (severe and mild) and punish them less than the latter. Design/methodology/approach This study adopts a 2 × 2 experimental design to manipulate corporate brand transgression levels (mild vs severe) and religios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
(127 reference statements)
0
11
0
Order By: Relevance
“…selling defective products, using misleading advertising, etc (Peterson et al , 2010), and this may indicate that religiosity will lead to less brand loyalty for transgressing brands. Consistent with this reasoning, Karaosmanoglu et al (2018) found that both intrinsic religiosity and extrinsic religiosity were positively related to punishing brands that are morally controversial. However, Karaosmanoglu et al (2018) examined brands that did not have religious positioning.…”
Section: The Effects Of Religiosity On Brand Loyaltymentioning
confidence: 59%
See 3 more Smart Citations
“…selling defective products, using misleading advertising, etc (Peterson et al , 2010), and this may indicate that religiosity will lead to less brand loyalty for transgressing brands. Consistent with this reasoning, Karaosmanoglu et al (2018) found that both intrinsic religiosity and extrinsic religiosity were positively related to punishing brands that are morally controversial. However, Karaosmanoglu et al (2018) examined brands that did not have religious positioning.…”
Section: The Effects Of Religiosity On Brand Loyaltymentioning
confidence: 59%
“…Consistent with this reasoning, Karaosmanoglu et al (2018) found that both intrinsic religiosity and extrinsic religiosity were positively related to punishing brands that are morally controversial. However, Karaosmanoglu et al (2018) examined brands that did not have religious positioning. Hence, it is important to investigate how religiosity relates to brand loyalty for religiously positioned brands when these brands engage in morally controversial actions.…”
Section: The Effects Of Religiosity On Brand Loyaltymentioning
confidence: 59%
See 2 more Smart Citations
“…Despite liberalization and globalization, religion still affects consumers (Abu-Alhaija et al, 2017;Al-Hyari et al, 2012). The growing influence of Islam on the market has illustrated the religious views of consumers in everyday business activities (Karaosmanoglu et al, 2018). According to Setyawati et al (2020), religiosity is seen as the key element that defines the behavior of individuals and facilitator the decision-making process of positive behavior.…”
Section: Structural Modelmentioning
confidence: 99%